Pembangunan Aplikasi Kesehatan Wajah Dengan Fitur Chat Berbasis Android Mobile Menggunakan Kotlin - Diva Amwal Maulana Supian; Ade Sukendar (Jurnal Tika, 2024)
Acne is a face health problem that makes some people who want to have a healthy face to be afraid. One of the causes of acne is due to air pollution. Although harmless, acne causes emotional and social disorders due to the discomfort caused by acne. Nowadays, people choose ready-to-use products that have been produced by a beauty clinic to treat their face. Evaluation of acne is traditionally done by dermatologists in the medical environment. However, the desire of the patient is to be able to consult with doctor using an easy way to do anytime and anywhere. With limit time, doctor also feel in terms of the amount of time to consult with the patient. Therefore, this research was done to build a face health app based on android mobile as an easy way to do a consultation called PIMPAD. With the PIMPAD app, patients an doctors can conduct consultations related to facial health through the chat feature available on the app. The end result of this study is to produce a face health app based on android mobile with chat features using a kotlin built as an easy way to do consultation between patients and doctors that can be used anytime and anywhere.